Reading the Bible in the African context: Assessing Africa's love affair with prosperity Gospel - Cezula, Ntozakhe (Stellenbosch Theological Journal, 2015)
The aim of this article is to examine Bible reading in the African context and the willingness and enthusiasm to embrace prosperity gospel in Africa. To achieve this objective, a discussion on the developments in biblical interpretation in Africa will first be presented. This will be done by examining three historical periods: colonial, independence and democratisation periods. This will be followed by an outline of migrations that have taken place from traditional religions to different versions of Christianity in different times in Africa. These migrations will be examined in connection with Bible translation. The relationship between prosperity gospel and African people in Africa will be discussed by considering the tools prosperity gospel uses to appeal to African people, namely the religio-cultural and socio-economic factors. The article will then provide its assessment of contextual reading in the prosperity gospel and a conclusion will follow.
free
Keywords: Bible Reading; Bible Translation; Contextual Reading; Pentecostalism; Prosperity Gospel